A Novel Small Molecular Antibody, HER2-Nanobody, Inhibits Tumor Proliferation in HER2-Positive Breast Cancer Cells In Vitro and In Vivo - Yan, Yan; Cheng, Xiao; Li, Lin; Zhang, Rumeng; Zhu, Yong; Wu, Zhengsheng; Ding, Keshuo (Frontiers in Oncology, 2021)
Breast cancer is the most common malignant cancer in women worldwide, especially in developing countries. Herceptin is a monoclonal antibody with an antitumor effect in HER2-positive breast cancer. However, the large molecular weight of Herceptin limited its employment. In this study, we constructed and screened HER2-nanobody and verified its tumor-suppressive effect in HER2-positive breast cancer cells. HER2-nanobody was established, filtrated, purified, and was demonstrated to inhibit cell total number, viability, colony formation and mitosis, and promote cell apoptosis in HER2-positive breast cancer cells in vitro. Treated with HER2-nanobody, tumor growth was significantly inhibited by both intratumor injection and tail intravenous injection in vivo. The phosphorylation of ERK and AKT was restrained by HER2-nanobody in HER2-positive breast cancer cells. RAS-RAF-MAPK and PI3K-AKT-mTOR are two important pathways involved in HER2. It was credible for HER2-nanobody to play the tumor suppressive role by inhibiting the phosphorylation of ERK and AKT. Therefore, HER2-nanobody could be employed as a small molecular antibody to suppress HER2-positive breast cancer.